2007
DOI: 10.1021/np0603018
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Metabolites from the Caribbean Sponge Aka coralliphagum

Abstract: The chemistry of the burrowing sponge Aka coralliphagum was investigated to identify chemically labile secondary metabolites. The HPLC-MS analysis of the two growth forms typica and incrustans revealed different metabolites. The previously unknown sulfated compounds siphonodictyals B1 to B3 (6-8), corallidictyals C (9) and D (10), and siphonodictyal G (11) were isolated, and their structures were elucidated by NMR and MS experiments. The compounds were tested in a DPPH assay, in antimicrobial assays against ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 20 publications
(80 reference statements)
2
40
0
Order By: Relevance
“…The oxidation of hydroquinone to quinone and the hydrogenation of the side-chain increased the antibacterial effect of these molecules [74]. Other hydroquinones isolated in 2007 from the Caribbean sponge Aka coralliphaga showed activity against S. aureus [75], confirming the results of Sullivan et al [76].…”
Section: Antibacterial Activitysupporting
confidence: 56%
“…The oxidation of hydroquinone to quinone and the hydrogenation of the side-chain increased the antibacterial effect of these molecules [74]. Other hydroquinones isolated in 2007 from the Caribbean sponge Aka coralliphaga showed activity against S. aureus [75], confirming the results of Sullivan et al [76].…”
Section: Antibacterial Activitysupporting
confidence: 56%
“…An aldehyde function is the distinctive feature of siphonodictyals A–D ( 123 – 126 ), G ( 127 ), B2 ( 128 ), and B3 ( 129 ), which have been isolated from Siphonodictyonspecies along with the relevant alcohols siphonodictyols G ( 130 ) and H ( 131 ) and siphonodictyoic acid ( 132 ); most of them were sulfated [100,101,102]. The isolated compounds were tested for antimicrobial activity (antibacterial, antifungal); it has been suggested that the different substituents on the aromatic moieties have an impact on activity and that the ortho -hydroquinone structure may be the active center of the molecules.…”
Section: Meroterpenes From Spongesmentioning
confidence: 99%
“…Structures with a fourth five-membered oxygen spiranic ring are cyclospongiaquinone-2 ( 193 ) [79,88], its analogs 7,8-dehydrocyclospongiaquinone-2 ( 194 ) and 9-epi-7,8-dehydrocyclospongiaquinone-2 ( 195 ) [89], and the corallidyctals A–D ( 196 – 199 ), isolated from the marine sponge Aka (= Siphonodictyon ) coralliphagum [102,143]. Both corallidictyal A ( 196 ) and B ( 197 ) inhibit PKC with an IC 50 = 28 μM, while assays addressing another cAMP-dependent kinase did not afford inhibition at concentrations of 300 μM, indicating its selectivity.…”
Section: Meroterpenes From Spongesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the assays revealed selectivity against the α isoform of PKC. Corallidyctals C and D were tested in antiproliferative assays using cultures of mouse fibroblasts and activity was linked to the presence of the ortho-hydroquinone moiety [28]. Assays on cytotoxic activity were performed against P-388, A-549, HT-29 and MEL-28 cells and against the KB, Bel-7402, PC-3M, Ketr 3 and MCF-7 human tumour cell lines.…”
Section: Fig 352 Avarol and Related Compoundsmentioning
confidence: 99%